Gait speed has comparable prognostic capability to six-minute walk distance in older patients with cardiovascular disease. (29th August 2020) - Kamiya, Kentaro; Hamazaki, Nobuaki; Matsue, Yuya; Mezzani, Alessandro; Corrà, Ugo; Matsuzawa, Ryota; Nozaki, Kohei; Tanaka, Shinya; Maekawa, Emi; Noda, Chiharu; Yamaoka-Tojo, Minako; Matsunaga, Atsuhiko; et al.
Abstract: Background: Although gait speed and six-minute walk distance are used to assess functional capacity in older patients with cardiovascular disease, their prognostic capabilities have not been directly compared. Methods: The study population was identified from the Kitasato University Cardiac Rehabilitation Database and consisted of 1474 patients ≥60 years old with a mean age of 72.2 ± 7.1 years that underwent evaluation of both usual gait speed and six-minute walk distance in routine geriatric assessment between 1 June 2008–30 September 2015. Both gait speed and six-minute walk distance were determined on the same day at hospital discharge. Results: Mean gait speed and six-minute walk distance in the whole population were 1.04 m/s and 381 m, respectively, and were strongly positively correlated ( r = 0.80, p < 0.001). A total of 180 deaths occurred during a follow-up of 2.3 ± 1.9 years. After adjusting for confounding factors, both gait speed (adjusted hazard ratio per 0.1 m/s increase: 0.87, 95% confidence interval: 0.81–0.93, p < 0.001) and six-minute walk distance (adjusted hazard ratio per 10-metre increase: 0.96, 95% confidence interval: 0.94–0.97, p < 0.001) were independent predictors of all-cause mortality. There was no significant difference in prognostic capability between gait speed and six-minute walk distance (c-index: 0.64 (95% confidence interval: 0.60–0.69) and 0.66 (95% confidence interval: 0.61–0.70), respectively, p = 0.357). Conclusions: Gait speed and six-minute walk distance showed similar prognostic predictive ability for all-cause mortality in older cardiovascular disease patients, indicating the potential utility of gait speed as a simple risk stratification tool in older cardiovascular disease patients.